2020
DOI: 10.3390/molecules25204743
|View full text |Cite
|
Sign up to set email alerts
|

A Rose Extract Protects the Skin against Stress Mediators: A Potential Role of Olfactory Receptors

Abstract: Olfactory receptors (ORs) are expressed and active in various human tissues, including the skin. Although the sense of smell plays an important physiological role in the regulation of mood and stress, a link between olfactive compounds, ORs, and skin stress has yet to be established. This study aims to investigate the role of newly identified skin ORs and agonists in the modulation of skin stress. Screening for odorant molecules was done with cAMP functional assay to identify OR agonists. RT-qPCR and immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…In CRCR1P, mutated OR10A6 showed a higher binding affinity (20 [5.29%] of 378 peptides) to HLA than that of other mutated genes (p < 0.0001). On the other hand, the mutated OR10A6 gene was not presented as a neoantigen (Table 2 ); therefore, OR10A6 18 must not be presented as a neoantigen peptide. As shown in Table 2 , representative mutated genes that could be chronologically traced by ctDNA showed either low binding affinities with HLA or low expression of mutated genes in a mutually exclusive manner.…”
Section: Resultsmentioning
confidence: 99%
“…In CRCR1P, mutated OR10A6 showed a higher binding affinity (20 [5.29%] of 378 peptides) to HLA than that of other mutated genes (p < 0.0001). On the other hand, the mutated OR10A6 gene was not presented as a neoantigen (Table 2 ); therefore, OR10A6 18 must not be presented as a neoantigen peptide. As shown in Table 2 , representative mutated genes that could be chronologically traced by ctDNA showed either low binding affinities with HLA or low expression of mutated genes in a mutually exclusive manner.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, its stimulatory effects on cell proliferation, migration, and gene expression of HAS2/3 and HBD-2 were all abrogated by the cAMP inhibitor, indicating that the α-ionone-induced activation of the cAMP signaling pathway is required for the beneficial effects of α-ionone on HaCaT cells. Although the mechanisms of how α-ionone increases intracellular cAMP levels remain unknown, it is noteworthy that α-ionone was recently identified as an agonist for 2 ORs, namely OR51E2 and OR10A6 ( 61 , 62 ). As these ORs have been detected to be expressed in human keratinocytes ( 62 ), it is quite possible that one or both may participate in the α-ionone-induced increase in cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of how α-ionone increases intracellular cAMP levels remain unknown, it is noteworthy that α-ionone was recently identified as an agonist for 2 ORs, namely OR51E2 and OR10A6 ( 61 , 62 ). As these ORs have been detected to be expressed in human keratinocytes ( 62 ), it is quite possible that one or both may participate in the α-ionone-induced increase in cAMP levels. Additional studies are needed to evaluate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro screening showed that the functional variant of OR10A6, which ranks among the most highly transcribed ORs in the olfactory epithelium ( Saraiva et al., 2019 ; Verbeurgt et al., 2014 ), is most sensitively tuned to Z4-11Al. OR10A6 may also be tuned to other odorants, such as cyclamen aldehyde ( Duroux et al., 2020 ), and further experiments are needed to map its entire agonist space.…”
Section: Discussionmentioning
confidence: 99%